2017
DOI: 10.3201/eid2307.161608
|View full text |Cite
|
Sign up to set email alerts
|

Novel Retinal Lesion in Ebola Survivors, Sierra Leone, 2016

Abstract: A lesion specific to Ebola virus disease showed an anatomical distribution suggesting neuronal transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 26 publications
(46 reference statements)
4
37
0
Order By: Relevance
“…The seroprevalence of T gondii IgG was 73% within our cohort, in keeping with uveitis secondary to T gondii being common in West Africa. 8 Retinal lesions suggestive of toxoplasmosis chorioretinitis were also present in 18.2% and 19% of survivors of EVD and local control individuals, respectively, in our previous study. 5 Therefore, a differential diagnosis for cataracts within survivors of EVD must include alternative etiologies that are common in the West African population.…”
Section: Cataractssupporting
confidence: 51%
“…The seroprevalence of T gondii IgG was 73% within our cohort, in keeping with uveitis secondary to T gondii being common in West Africa. 8 Retinal lesions suggestive of toxoplasmosis chorioretinitis were also present in 18.2% and 19% of survivors of EVD and local control individuals, respectively, in our previous study. 5 Therefore, a differential diagnosis for cataracts within survivors of EVD must include alternative etiologies that are common in the West African population.…”
Section: Cataractssupporting
confidence: 51%
“…Fourteen Ebola survivors met the eligibility criteria of at least one identified Ebola retinal lesions on UWF retinal imaging in keeping with the findings of our previous study 1. All fourteen were recalled and attended the clinic for examination including OCT of accessible Ebola retinal lesions.…”
Section: Methodsmentioning
confidence: 82%
“…The demonstration of infectious virus in the CSF of patients is a clear indication that the virus is capable of entering and replicating within the immunoprivileged locale of the CNS (8, 15, 21). The demonstration of viral persistence in other immunoprivileged sites, such as the eye and testes, also raises the question of viral persistence in the CNS (23, 26, 50, 51).…”
Section: Discussionmentioning
confidence: 99%
“…However, a number of studies have demonstrated the presence of infectious virus within the cerebrospinal fluid (CSF) of Ebola survivors, months after initial discharge from hospital (8, 15, 21). In addition, there have been numerous reports of ocular involvement following Ebola virus disease, leading to persistent infection (2226). Taken together, these observations demonstrate that Ebola virus is capable of crossing both the blood-ocular and blood-brain barriers to gain entry to otherwise immune-privileged sites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation